2021
DOI: 10.3390/bios12010014
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Powered Inertial Microfluidic Syringe-Tip Centrifuge

Abstract: Conventional sample preparation techniques require bulky and expensive instruments and are not compatible with next-generation point-of-care diagnostic testing. Here, we report a manually operated syringe-tip inertial microfluidic centrifuge (named i-centrifuge) for high-flow-rate (up to 16 mL/min) cell concentration and experimentally demonstrate its working mechanism and performance. Low-cost polymer films and double-sided tape were used through a rapid nonclean-room process of laser cutting and lamination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Correspondingly, the sample throughput of the planar spiral centrifuge is much bigger. Xiang and Ni [11] even included a centrifuge with multi-layer parallel microchannels designed to increase the sample processing capacity. Of course, this also means that the design and manufacture of the planar spiral centrifuge is also relatively difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the sample throughput of the planar spiral centrifuge is much bigger. Xiang and Ni [11] even included a centrifuge with multi-layer parallel microchannels designed to increase the sample processing capacity. Of course, this also means that the design and manufacture of the planar spiral centrifuge is also relatively difficult.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the sample processing capacity, Xiang et al [11] reported a manually operated inertial microfluidic centrifuge with a four-channel parallel structure, which has the advantages of simple operation and high flow processing. However, this microchannel has a disc-like helical structure; the inner ring channel radius is small, and the outer channel radius is large, which means the inertial lift force is not constant.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al reported a hand-powered inertial microfluidic syringe tip centrifuge with a high flow rate of 16 mL min −1 . [213] This offers a potential solution to the traditionally large centrifuges that are often needed for sample management alongside biosensing devices. The centrifuge consists of a syringe tip flow stabilizer and a syringe filter-like inertial microfluidic concentrator.…”
Section: Sample Preparation and Manual Handlingmentioning
confidence: 99%
“…A prominent advantage of inertial microfluidics is that it can be operated by simply driving the flow within a specific flow-rate range. Therefore, the mechanical force provided by the compression spring 154 or the power generated by manually pushing the syringe 70,[155][156][157][158] can be used to drive the sample flow in inertial microfluidics, which enables electricity-free operation for use in low-resource settings. We believe that a growing number of inertial microfluidics-based instruments will be developed in the future for widespread biomedical applications.…”
Section: Commercial Instruments For Practical Applicationsmentioning
confidence: 99%